Improvement of the Structural and Electrical Properties of PVA through the Addition of Bi₂O₃ and SiO₂ Nanoparticles for Electronic Devices - Ali Emad Nief; A. R. Abdulridha (International Journal of Computational and Experimental Science and Engineering, 2025)
This study focuses on the preparation of (PVA/Bi2O3/SiO2) nanocomposites using the solution casting method, incorporating different amounts (0, 2, 4, 6, and 8 wt.%) of Bi2O3 and SiO2 nanoparticles into polyvinyl alcohol (PVA) polymer. The XRD results revealed that PVA exhibited an amorphous nature, which transformed into a polycrystalline structure with the incorporation of high loading (8 wt.%) Bi2O3 and SiO2 nanoparticles. The dielectric constant and loss of the (PVA/Bi2O3/SiO2) nanocomposite were observed to decrease with increasing frequency, whereas they improved with the content ratio of Bi2O3 and SiO2 nanoparticles. The A.C. conductivity of the (PVA/Bi2O3/SiO2) nanocomposite increases with the frequency and the concentration of Bi2O3 and SiO2 nanoparticles. Ultimately, this outcome indicates that the (PVA/Bi2O3/SiO2) nanocomposites have potential applications in electronic properties.